Analysis of the Impact of Agroindustry, Packaging Technology, and Local Product Branding on the Value Added of Banana Products in Makassar - Megavitry, Rissa (Westscience Press, 2025)
This study investigates the impact of agroindustry, packaging technology, and local product branding on the value added to banana products in Makassar. Using a quantitative approach, data was collected from 145 banana producers in Makassar, with responses measured using a Likert scale. The study employed Structural Equation Modeling - Partial Least Squares (SEM-PLS 3) for data analysis. The results revealed that agroindustry development, packaging technology, and local product branding all have significant positive impacts on the value added to banana products. Agroindustry showed a moderate positive relationship, while packaging technology had a stronger influence. Local product branding, although important, showed a weaker effect. The study emphasizes the importance of integrating advanced agroindustry practices, modern packaging technologies, and effective branding strategies to enhance the competitiveness and economic viability of banana products in Makassar. This research offers practical insights for stakeholders seeking to improve the value addition of agricultural products and provides a foundation for further studies in the agroindustry sector.